Sub-chronic microcystin-LR renal toxicity in rats fed a high fat/high cholesterol diet. (April 2021) - Arman, Tarana; Lynch, Katherine D.; Goedken, Michael; Clarke, John D.
Abstract : Microcystin-LR (MCLR) is a liver and kidney toxin produced by cyanobacteria. Recently, it was demonstrated that MCLR exposure drives the progression of high fat/high cholesterol (HFHC) induced nonalcoholic fatty liver disease (NAFLD) to a more severe state. NAFLD is also a risk factor for chronic kidney disease (CKD), and the current study investigated MCLR renal toxicity in the context of an HFHC diet. Sprague Dawley rats were fed either a control diet or an HFHC diet for 10 weeks. After 6 weeks of diet, animals were administered either vehicle, 10 μg/kg, or 30 μg/kg MCLR via intraperitoneal injection every other day for 4 weeks. HFHC diet alone increased the renal glomerular change histopathology score, and 30 μg/kg MCLR exposure increased this score in both the control group and the HFHC group. In contrast, 30 μg/kg MCLR caused greater proteinuria and cast formation and decreased protein phosphatase 1 and 2A protein expression in the HFHC group. Urinary excretion of KIM-1 increased, but albumin and tamm-horsfall protein did not change after MCLR exposure. The general concordance between KIM-1, polyuria, proteinuria, and renal casts after MCLR exposure suggests that proximal tubule cell damage contributed to these connected pathologies. The control group adapted to repeated MCLR exposure by increasing the urinary elimination of MCLR and its metabolites, whereas this adaptation was blunted in the HFHC group. These data suggest an HFHC diet may increase the severity of certain MCLR-elicited renal toxicities. Highlights: HFHC diet increased severity of MCLR induced casts and proteinuria. Urinary KIM-1 levels increased after MCLR exposure. PP1 and PP2A protein levels decreased after MCLR exposure only in the HFHC group. HFHC diet decreased the metabolism and total urinary elimination of MCLR.